Elite road cycling sprinters: quantifying the demands of the final hour - Menaspa, P.; Martin, D. T.; Abbiss, C. R. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
The demands of uphill and time trial performances and the physiological characteristics of professional road cyclists have been well documented. Despite the importance of sprinting to the overall outcomes of a race and the high number of sprint finishes within professional road cycling (Menaspà et al. 2013a), research examining the demands of professional road sprint cycling is limited to a couple of preliminary studies (Menaspà et al. 2013a; Menaspà et al. 2013b). The aim of this study was to examine and describe the demands of road cycling sprint competitions in professional male cycling, with particular focus on the lead-up phase prior to the final sprint. Methods